ANALISIS TINGKAT KONSENTRASI BELAJAR MATEMATIKA SISWA KELAS VII-H SMPN 2 MAJALAYA KARAWANG - Rontauli Sihotang; Hotmaulina Sihotang; Stevi Natalia (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2023)
Since a government policy that mandated social isolation or restrictions on social interaction to prevent the spread of the COVID-19 virus, online education has been practiced in Indonesia. Various communication tools, such as Google Classroom, Google Meet, Zoom, Edmodo, or WhatsApp, are used for online learning activities. In the current state of online education, many factors contribute to students becoming sluggish or disinterested in their studies, such as the fact that it requires a high level of concentration, time, and energy, as well as feelings of compulsion to abandon some activities that, in comparison to learning, are more enjoyable. others, both positive and negative exercises. Therefore, the purpose of this study is to investigate the learning concentration level of students in class VII-H at SMPN 2 Majalaya Karawang. by employing qualitative exploratory techniques. The findings indicate that students in grades VII through H have a moderate level of concentration.